Of Famines and Females: The Politics of Lakṣmī Bratakathās of Bengal. (3rd August 2017) - Sengupta, Saswati; Purkayastha, Sharmila
Abstract : Lakṣmī Bratakathās in Bengal are religious narratives of the eponymous Hindu goddess who presides over prosperity symbolized through an abundance of rice. The reciting of these Lakṣmī Bratakathās is a sacral duty of the women of the Bhadralok, which remains a popular practice even today. The period of rise and proliferation of these specific narratives, from the eighteenth century onwards, coincides with catastrophic famines with which imperialism in Bengal starts and ends and which provide the historical motivations for requesting the intervention of the goddess of plenty. But there is a deliberate mystification of hunger as Lakṣmī displaces the problem of famine onto the axes of vice and virtue, which are specifically located in the transgressive figure of the 'New Woman'. Since this is also the period which ushers in a new construction of gender relations, the displacement in these Bratakathās is of critical importance. The article examines the ideological framing of hunger by locating the matrices of the colliding and colluding histories of colonialism, class and gender.